America's best friend? Poland's Atlanticist-European strategy - Kai-Olaf Lang (Stiftung Wissenschaft und Politik (SWP), 2003)
Polish President Kwasniewski was met by much flattery from his hosts during his visit to America in mid-January. President Bush described Poland as the 'best friend of the United States' in Europe, while Secretary of State Powell referred to Poland as an 'equal partner.' Although this appreciation is nothing new, it reflects Poland's particular loyalty towards the United States in the current world-political situation. The sweeping solidarity with the U.S. in the Iraq question, as well as the decision taken at the end of to equip the Polish Air Force with US fighter jets, has consolidated the positive image of Poland in the U.S. In Europe, on the other hand, this has nourished suspicions of Polish pro-Americanism. Should Poland, as a member of the EU, over-identify with American positions, it would strengthen the camp of the firmly American and Atlanticoriented countries, therefore bolstering co-ordination with Great Britain. On the other hand, EU membership could lead to an increased Europeanisation of Poland's Atlanticism in the medium term.(SWP Comments / SWP)
Keywords: 320